ANALISIS RESIKO KANKER PAYUDARA (BREAST CANCER) MENGGUNAKAN FUZZY INFERENCE SYSTEM (FIS) MODEL MAMDANI - Milyun Ni’ma Shoumi; Arie Rachmad Syulistyo (Universitas Janabadra, 2021)
Breast cancer is a type of malignant cancer, in which cells form in the breast tissue, and is the most common type of cancer - apart from skin cancer - and is ranked second (after lung cancer) the type of cancer that causes death. Every year thousands of people die from cancer due to limited medical resources and the inability of society to use existing information sources effectively. The most efficient way and one of the means of protection against breast cancer is early diagnosis. In this study, a system to analyze the risk of breast cancer was developed using the Mamdani model of Fuzzy Inference System (FIS). By using 6 input variables, the developed Mamdani FIS is able to produce an accuracy of 85% with 20 data used. Keywords: cancer, breast cancer, fuzzy inference system,,fuzzy logic, Mamdani model.